Determinant of Farmers' Readiness Level and Their Strategies in Independent Palm Oil Plantations in Kapuas Hulu Regency - Risyadi, Irfan; dolorosa, Eva; Kurniati, Dewi (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The development of oil palm plantations in Indonesia is increasing because oil palm is one of the most important plantations in the economy of Indonesia. Sustainable management of oil palm is vital because it could reduce threats to natural resources, deforestation, expansion of land in ways that are not environmentally friendly such as by burning, and damage to peat ecosystems. The study aimed to determine farmers' readiness level in implementing ISPO certification for independent oil palm plantations in Kapuas Hulu Regency and to determine the right strategic priorities for managing independent oil palm plantations based on sustainable palm oil (ISPO) in Kapuas Hulu Regency. The data were analyzed descriptively with Analytical Hierarchy Process (AHP). The data was collected from 100 respondents taken by purposive sampling. The results show that overall the application level of compliance with laws and regulations is 24.8%, implementing good plantation practices is 31.33%, environmental management of natural resources and biodiversity is 42.5%, implementing transparency of 28.5%, and sustainably increasing business by 40%. Overall the average level of ISPO implementation achievement among the independent oil palm smallholders in Kapuas Hulu District is low, with a percentage of 30.8%. The optimal top priority for the strategy of independent oil palm plantations is mediation between conflicting parties, independent oil palm farmer groups, transparency regarding environmental impacts, extension agents in the plantation division and quality improvement of production. Keywords: farmers' readiness level, palm oil, ISPO, independent smallholders, AHP